FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN TANGGUNG JAWAB LINGKUNGAN DALAM LAPORAN TAHUNAN (Studi Empiris pada Perusahaan yang Terdaftar di PROPER dan BEI Periode 2008-2010) - Rochman Effendi; Yosefa Sayekti; Rahma Rina Wijayanti (Universitas Jember, 2012)
This research was aimed to obtain empirical evidence about factors influencing environmental responsibility disclosure in the company`s annual report. The factors used in this research were profitability, company size, government regulation, corporate status, and industry sector. The measurement of the level environmental liability disclosure was based on the GRI (2006). The type of this research was quantitative and used secondary data based on companies` annual reports of the listed companies in PROPER and Indonesia Stock Exchange during period 2008 - 2010. The results of this research indicated that the company size variable was statistically significant and positively influential on the rate of environmental responsibility disclosure, while corporate status of non PMA (BUMN and PMDN) and industry sector which had the highest environmental compliance according to PROPER were statistically significant on the rate of environmental responsibility disclosure. However, profitability and government regulation did not affect significantly to the rate of environmental responsibility disclosure. Keywords: GRI, environmental responsibility disclosure, profitability, company size, government regulation, corporate status, and industry sector